APLIKASI PENJUALAN KUE TRADISIONAL ONLINE DI MAKASSAR DENGAN FITUR STANDARDISASI PRODUKSI - marlina, Marlina; Sofyan, Mohammad; Witanto, Karina Levina (JITU, 2018)
The problem in this research is traditional cake sales which is done offline and not yet refer to a standardization. So the purpose of this study is to build an application used to make sales of traditional cakes online with standardization features of production. Initial research conducted by the authors resulted in that human resources (traditional cake craftsmen) are available but the sales medium is limited. Especially with the sales process is still manual to add a number of difficulties that must be faced. Therefore the author makes a traditional cake sales application that brings together sellers and buyers. Web-built application using PHP programming language and MySQL database. Standardization for traditional cakes has not existed to date so in formulating the items used as traditional cake benchmarks, the authors have conducted research that produces the standards to be measured are size, material, presentation, and taste. From the results of application implementation testing conducted with a questionnaire on 15 respondents with average results of 85.6% (strongly agree), it can be concluded that the application can be used and accepted.